Cheating in Iran: An Examination of Academic Dishonesty Through the Lens of Situational Action Theory - Shadmanfaat, Seyyedeh Masoomeh (Shamila) (International criminal justice review, 2025)
Academic dishonesty has recently attracted the attention of scholars worldwide in the aftermath of severe breaches of academic rules of conduct. As today's students are tomorrow's leading academics and professionals, it continues to be of importance to understand the basic explanatory mechanisms of academic dishonesty. The present cross-cultural inquiry explores academic dishonesty through the lens of situational action theory (SAT). Specifically, this paper explores the connection between criminogenic propensity and criminogenic exposure, and its impact on academic misconduct. We analyze self-reported data from a random sample of 378 Iranian students. Multivariate regression results, examining both direct and interactional relationships, demonstrate that the key propensity–environment hypotheses of SAT are generally supported as morality, self-control, and perceived deterrence all play a role in explaining academic misconduct. Specific findings, study limitations, and directions for future research are discussed.